Semiconducting thin films of CuSbS2 - Messina, Sarah; Hernández, Paz; Peña Méndez, Yolanda (Universidad Autónoma de Nuevo León, 2011)
In this paper we present a method to produce polycristalline CuSbS2 thin films through a solid-state reaction at 350ºC and 400ºC involving thin film multilayer of Sb2S3-CuS or Cu2-xSe by chemical bath deposition technique. The formation of ternary compound was confirmed by X-ray diffraction (XRD). A direct optical band gap of approx. 1.57 eV and a p-type electrical conductivity of 10^-3 (?cm)^-1 were measured. These optoelectronic characteristics show perspective for the use of CuSbS2 as a suitable absorber material in photovoltaic applications.